Well Testing and Power Plant Scenario Analysis for Hverahlid Geothermal Field - Mesay Biru 1989- (2020)
In this thesis, different methods for analyzing well test data to estimate capacity of a geothermal field are evaluated, using the Hverahlid geothermal field in the Hengill geothermal system, SW-Iceland as a case study. The thesis includes analysis of data from step-rate injection tests, temperature and pressure analysis, discharge test analysis and different power plant scenario analysis. The power plant scenario analysis was conducted to determine the optimum electric power output and choose the most efficient energy conversion technology. The computer software WellTester is used for the analysis of step-rate injection tests and the results are compared with results from other high temperature geothermal fields. Temperature and pressure profiles are analysed for each well to estimate the formation temperature and initial reservoir pressure. Total mass flow rate (kg/s), enthalpy (kJ/kg) and flow characteristics are calculated using the lip pressure method. The Engineering Equation Solver (EES) was used for modelling. The estimated values of transmissivity (T) for wells HE-36, HE-53 and HE-61 ranges from 4.2*10-8 to 7.2 *10-7 m3/Pa*s, from the injection test, whereas the storage coefficient values (S) range from 2.3*10-8 to 4.3*10-7 m/Pa. The estimated values for the skin factor are negative indicating that the wells are well stimulated and in good connection with the surrounding reservoir. The evaluation of temperature for wells HE-36, HE-53 and HE-61 suggests that reservoir temperature is in the range of 270-320°C and reservoir pressure 132 bar at 1750 m (HE-36), 118 bar at 1500 m (HE-53) and 85 bar at 1140 m for HE-21 respectively. The evaluated fluid enthalpy for wells HE-21, HE-36 and HE-53 is in the range of 1352 to 1683 kJ/kg, with the steam flow ranging from 6 to 29 kg/s with an assumed separation pressure of 17 bar-g. Three power plant scenarios for Hverahlid are studied. Scenario 1 is a single flash power plant. The power output of the four wells involved is 49.0 MWe. Scenario 2 is a double flash power ...